Triticum monococcum lines with distinct metabolic phenotypes and phloem‐based partial resistance to the bird cherry–oat aphid Rhopalosiphum padi. (29th February 2016) - Greenslade, A.F.C.; Ward, J.L.; Martin, J.L.; Corol, D.I.; Clark, S.J.; Smart, L.E.; Aradottir, G.I.
Abstract: Crop protection is an integral part of establishing food security, by protecting the yield potential of crops. Cereal aphids cause yield losses by direct damage and transmission of viruses. Some wild relatives of wheat show resistance to aphids but the mechanisms remain unresolved. In order to elucidate the location of the partial resistance to the bird cherry–oat aphid, Rhopalosiphum padi, in diploid wheat lines of Triticum monococcum, we conducted aphid performance studies using developmental bioassays and electrical penetration graphs, as well as metabolic profiling of partially resistant and susceptible lines. This demonstrated that the partial resistance is related to a delayed effect on the reproduction and development of R. padi. The observed partial resistance is phloem based and is shown by an increase in number of probes before the first phloem ingestion, a higher number and duration of salivation events without subsequent phloem feeding and a shorter time spent phloem feeding on plants with reduced susceptibility. Clear metabolic phenotypes separate partially resistant and susceptible lines, with the former having lower levels of the majority of primary metabolites, including total carbohydrates. A number of compounds were identified as being at different levels in the susceptible and partially resistant lines, with asparagine, octopamine and glycine betaine elevated in less susceptible lines without aphid infestation. In addition, two of those, asparagine and octopamine, as well as threonine, glutamine, succinate, trehalose, glycerol, guanosine and choline increased in response to infestation, accumulating in plant tissue localised close to aphid feeding after 24 h. There was no clear evidence of systemic plant response to aphid infestation.